Combination of EP4 antagonist MF-766 and anti-PD-1 promotes anti-tumor efficacy by modulating both lymphocytes and myeloid cells. (1st January 2021) - Wang, Yun; Cui, Long; Georgiev, Peter; Singh, Latika; Zheng, Yanyan; Yu, Ying; Grein, Jeff; Zhang, Chunsheng; Muise, Eric S.; Sloman, David L.; Ferguson, Heidi; Yu, Hongshi; et al.
ABSTRACT: Prostaglandin E2 (PGE2 ), an arachidonic acid pathway metabolite produced by cyclooxygenase (COX)-1/2, has been shown to impair anti-tumor immunity through engagement with one or more E-type prostanoid receptors (EP1-4 ). Specific targeting of EP receptors, as opposed to COX-1/2 inhibition, has been proposed to achieve preferential antagonism of PGE2 –mediated immune suppression. Here we describe the anti-tumor activity of MF-766, a potent and highly selective small-molecule inhibitor of the EP4 receptor. EP4 inhibition by MF-766 synergistically improved the efficacy of anti-programmed cell death protein 1 (PD-1) therapy in CT26 and EMT6 syngeneic tumor mouse models. Multiparameter flow cytometry analysis revealed that treatment with MF-766 promoted the infiltration of CD8 + T cells, natural killer (NK) cells and conventional dendritic cells (cDCs), induced M1-like macrophage reprogramming, and reduced granulocytic myeloid-derived suppressor cells (MDSC) in the tumor microenvironment (TME). In vitro experiments demonstrated that MF-766 restored PGE2 -mediated inhibition of lipopolysaccharide (LPS)-induced tumor necrosis factor (TNF)-α production in THP-1 cells and human blood, and PGE2 -mediated inhibition of interleukin (IL)-2-induced interferon (IFN)-γ production in human NK cells. MF-766 reversed the inhibition of IFN-γ in CD8 + T-cells by PGE2 and impaired suppression of CD8 + T-cells induced by myeloid-derived suppressor cells (MDSC)/PGE2. In translational studies using primary human tumors, MF-766 enhanced anti-CD3-stimulated IFN-γ, IL-2, and TNF-α production in primary histoculture and synergized with pembrolizumab in a PGE2 high TME. Our studies demonstrate that the combination of EP4 blockade with anti-PD-1 therapy enhances antitumor activity by differentially modulating myeloid cell, NK cell, cDC and T-cell infiltration profiles.